2007
DOI: 10.1073/pnas.0700384104
|View full text |Cite
|
Sign up to set email alerts
|

High-speed mapping of synaptic connectivity using photostimulation in Channelrhodopsin-2 transgenic mice

Abstract: To permit rapid optical control of brain activity, we have engineered multiple lines of transgenic mice that express the lightactivated cation channel Channelrhodopsin-2 (ChR2) in subsets of neurons. Illumination of ChR2-positive neurons in brain slices produced photocurrents that generated action potentials within milliseconds and with precisely timed latencies. The number of light-evoked action potentials could be controlled by varying either the amplitude or duration of illumination. Furthermore, the freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
373
4
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(395 citation statements)
references
References 25 publications
16
373
4
2
Order By: Relevance
“…5d) was B20 mm (corresponding to B0.7°and B0.07°of visual angle in mice and humans, respectively), contrasts with a previous report, which argued that ChR2 cellular excitation requires very large (4100 mm) excitation spots 12,14 . A recent report suggested that a retinal prosthetic system with cellular activity emulating natural RGCs encoding strategies, could underlie the restoration of vision to normal performance levels 9 .…”
Section: Resultscontrasting
confidence: 88%
See 1 more Smart Citation
“…5d) was B20 mm (corresponding to B0.7°and B0.07°of visual angle in mice and humans, respectively), contrasts with a previous report, which argued that ChR2 cellular excitation requires very large (4100 mm) excitation spots 12,14 . A recent report suggested that a retinal prosthetic system with cellular activity emulating natural RGCs encoding strategies, could underlie the restoration of vision to normal performance levels 9 .…”
Section: Resultscontrasting
confidence: 88%
“…A pattern photo-stimulation system for artificially controlling neural activity in a vision prosthesis or for general neurostimulation applications is not expected to have this limitation (due to minimal light scattering in the inner retinal layers) and will ideally allow cellular-resolution, rapid, massively parallel, light-efficient stimulation across macroscopic (millimeter-scale) coverage areas. To date, however, optical excitation of optogenetically targeted populations is often delivered nonspecifically to the whole population using wide-field flashes with intense lamps 1,3,10 , LEDs (light-emitting diodes) and optical fibre coupled illumination 11,12 or in simple patterns using rapid random-access laser deflection 13,14 , digital micromirror arrays 8,9,[15][16][17][18] and micro-LED arrays 6,19 .…”
mentioning
confidence: 99%
“…Many genetically encoded tools to both monitor and manipulate various physiological properties of neurons have been developed in recent years [2][3][4][5][6][7][8][29][30][31][32] . These include fluorescent reporters of synaptic transmission and ion concentrations, as well as reagents to modulate neuronal excitability and neurotransmitter release.…”
Section: Discussionmentioning
confidence: 99%
“…6 We have already demonstrated that the responses induced by various stimulus frequencies (Hz) in ChR2-transduced rats are in no way inferior to those in normal rats, 7 as supported by the finding that ChR2-induced photocurrents are extremely fast. 8,9 Visual function was also well analysed by using transgenic rats with ChR2 transduction into RGCs: the spatial frequencies based on behavioural responses of photoreceptordegenerated ChR2 transgenic rats were the same as those of normal rats. 10 These studies indicate that transfer of the ChR2 gene into the remaining retinal neurons is a useful method for restoring vision in progressed RP.…”
Section: Introductionmentioning
confidence: 99%